Inovações tecnológicas, big techs e o capitalismo contemporâneo - Bortotto, Giovanna Borges (2022)
The rising technological innovation today is part of a previous process of broad technological development, deeply linked to the current economical dynamics. We recognize the historical link between the application of technology and capitalist accumulation, dating back to the First and consecutive technoscientific revolutions. In the present dissertation, we aim to fathom the many forms through which technique has been embedded into productive processes, the circulation sphere, finance, and other means of wealth appropriation. Mobile devices and connections, digital platforms, Artificial Intelligence, Information and Communication Technologies (ICTs), and big data (large-scale data and information processing) are some of the techs we investigate ‒ in chapter one ‒, seeking to locate them within the social and economic scenario. We note a group of companies hold a great share of the technology market, which is highly centralized: big tech companies, huge companies that focus on producing and reproducing new technologies. We examine ‒ in chapter two ‒ the GAMFA (Google, Apple, Microsoft, Facebook, and Amazon) and BAT (Baidu, Alibaba, and Tencent) groups, searching for elements that could describe their property structure and operation, certainly relevant in this process. Our analysis covers capitalist techno-organizational conditions through an investigation of some Marxian categories. For this purpose, in chapter three, we delve into the crossing between technique and the distinct levels of capitalist reproduction. Lastly, in chapter four, we enquire into the aftermath of the so-called economic "datafication" and big data's most recent impacts, taking into account the hypothesis of technology prevailing as the backbone apparatus of capitalism.